Validation of thermal dynamics during Hyperthermic IntraPEritoneal Chemotherapy simulations using a 3D-printed phantom - Löke, Daan R.; Kok, H. Petra; Helderman, Roxan F. C. P. A.; Franken, Nicolaas A. P.; Oei, Arlene L.; Tuynman, Jurriaan B.; Zweije, Remko; Sijbrands, Jan; Tanis, Pieter J.; Crezee, Johannes (Frontiers in Oncology, 2023)
CytoReductive Surgery (CRS) followed by Hyperthermic IntraPeritoneal Chemotherapy (HIPEC) is an often used strategy in treating patients diagnosed with peritoneal metastasis (PM) originating from various origins such as gastric, colorectal and ovarian. During HIPEC treatments, a heated chemotherapeutic solution is circulated through the abdomen using several inflow and outflow catheters. Due to the complex geometry and large peritoneal volume, thermal heterogeneities can occur resulting in an unequal treatment of the peritoneal surface. This can increase the risk of recurrent disease after treatment. The OpenFoam-based treatment planning software that we developed can help understand and map these heterogeneities. In this study, we validated the thermal module of the treatment planning software with an anatomically correct 3D-printed phantom of a female peritoneum. This phantom is used in an experimental HIPEC setup in which we varied catheter positions, flow rate and inflow temperatures. In total, we considered 7 different cases. We measured the thermal distribution in 9 different regions with a total of 63 measurement points. The duration of the experiment was 30 minutes, with measurement intervals of 5 seconds. Experimental data were compared to simulated thermal distributions to determine the accuracy of the software. The thermal distribution per region compared well with the simulated temperature ranges. For all cases, the absolute error was well below 0.5°C near steady-state situations and around 0.5°C, for the entire duration of the experiment. Considering clinical data, an accuracy below 0.5°C is adequate to provide estimates of variations in local treatment temperatures and to help optimize HIPEC treatments.